First-principles hybrid functional study of the electronic structure and charge carrier mobility in perovskite CH3NH3SnI3 - 伍丽娟 赵宇清 陈畅文 王琳芝 刘标 蔡孟秋 (中国物理B：英文版, 2016)
We calculate the electronic properties and carrier mobility of perovskite CH3NH3SnI3 as a solar cell absorber by using the hybrid functional method. The calculated result shows that the electron and hole mobilities have anisotropies with a large magnitude of 1.4 × 104cm2·V-1·s-1 along the y direction. In view of the huge difference between hole and electron mobilities, the perovskite CH3NH3 Sn I3can be considered as a p-type semiconductor. We also discover a relationship between the effective mass anisotropy and electronic occupation anisotropy. The above results can provide reliable guidance for its experimental applications in electronics and optoelectronics.